Floating macro- and microplastics around the Southern Ocean: Results from the Antarctic Circumnavigation Expedition. (March 2020) - Suaria, Giuseppe; Perold, Vonica; Lee, Jasmine R.; Lebouard, Fabrice; Aliani, Stefano; Ryan, Peter G.
Highlights: Very low concentrations of floating macro and microplastics found around Antarctica. Mean densities of 0.03 macrolitter items·km −2 and 187.6 microplastics·km −2 . Plastic densities are one order of magnitude lower than in adjacent temperate waters. The Subtropical Front seems to be a barrier to the dispersal of drifting plastics. Abstract: While macroplastics have been washing up on Southern Ocean islands for decades and microplastics have been found in seabirds from the region since 1960, there are still relatively few quantitative data on the amount of plastic pollution, especially with regard to floating plastics, at high southern latitudes. We present a baseline estimate of the abundance of floating plastics around the Southern Ocean from a survey of floating macro-, meso- and microplastic pollution conducted during the Antarctic Circumnavigation Expedition in 2016/17. A total of 40 net trawls and 626 h of observation were performed during this survey. Of these, 33 net samples and 552 h of observation were made in polar waters south of the Subtropical Front (STF). Only 5 microplastics and 17 macrolitter items were observed south of the STF, confirming the Southern Ocean as the region with the lowest concentrations of plastic pollution globally. The mean concentrations of floating macrolitter (0.02–0.03 items·km −2 ) and small plastic fragments (188 ± 589 particles·km −2 ) south of the STF were one order of magnitude lower than in adjacent temperate waters north of the STF, which suggests that the STF acts as a barrier to the southward transport of floating debris. Despite their much lower density, the mass of macroplastics was similar to that of floating microplastics in the Southern Ocean.